THE IMPACT OF STUDENTS’ MENTAL HEALTH IN ENGLISH ONLINE LEARNING DURING COVID-19 PANDEMIC AT SMA NEGERI 2 SOJOL - Umi, Lia; Muhammad Ihsan; Amelia, Yuni; Pettawali, M. Tamrin AM. S. (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2021)
The global pandemic that set by the World Health Organization on January 30, 2020 as a result of the new disease of Covid-19 has made many major changes, one of them in education where learning system are done through online. Online learning policies during the Covid-19 pandemic are the main solution to keeping the learning process going.This thesis aims to find out what impact of English online learning has on students' mental health during the covid-19 pandemic at SMA Negeri 2 Sojol and To find out what factors hindered students in the process of English online learning at SMA Negeri 2 Sojol. In this research, the researcher applied a descriptive qualitative research which were located at SMA Negeri 2 Sojol. Data sources obtained through primary and secondary data. Data collection techniques used are questionnaire and interviews. Based on the results of the questioner showed that they tend to just felt bored, difficult to concentrate, feelings of fear or worry if they are unable to collect tasks on time as well as their difficulty in understanding the material when English online learning during the covid-19 pandemic. Where it is caused by several factors such as poor internet network, residential environment and also monotonous teaching techniques from English teachers.